Wall grid structure for interior scene synthesis. (February 2015) - Xu, Wenzhuo; Wang, Bin; Yan, Dong-Ming
Abstract: We present a system for automatically synthesizing a diverse set of semantically valid, and well-arranged 3D interior scenes for a given empty room shape. Unlike existing work on layout synthesis, that typically knows potentially needed 3D models and optimizes their location through cost functions, our technique performs the retrieval and placement of 3D models by discovering the relationships between the room space and the models׳ categories. This is enabled by a new analytical structure, called Wall Grid Structure, which jointly considers the categories and locations of 3D models. Our technique greatly reduces the amount of user intervention and provides users with suggestions and inspirations. We demonstrate the applicability of our approach on three types of scenarios: conference rooms, living rooms and bedrooms. Abstract : Graphical abstract: Abstract : Highlights: A novel structure that learns the arrangement and symmetry information of a room. An interior scene synthesis method that generates plausible interior scenes. A context-based algorithm that automatically extracts the front directions of models. Several meaningful criteria for the assessment of interior scenes.